A Disaggregate Model of the Demand for Intercity Freight Transportation - Winston, Clifford (Econometrica, 1981)
[Previous work in the demand for freight transportation has followed an aggregate approach without any consideration of the underlying behavior of the individuals who actually make mode-choice decisions. In this paper, we analyze mode-choice behavior at the level of the individual decision maker with the purpose of applying the results to various issues related to intermodal competition. Based on a theory of shipper/receiver behavior, a random expected utility model suitable for econometric analysis is developed and estimated. Data for the empirical analysis consists of a large number of shipments covering a wide range of commodities, lengths of haul, and origin-destination pairs. The transport modes considered in the analysis are regulated and unregulated motor freight and rail. The central conclusion is that each mode has an opportunity to attract a substantial amount of traffic in particular markets through either service or price competition. In general, however, it appears that the opportunities for attracting traffic are greater through lower rates than improvements in service quality.]